Development of Self-Evaluation Instruments Website-Based Teacher Professional Education Study Program At Lembaga Pendidikan Tenaga Kependidikan (LPTK) Institut Agama Islam Negeri Pontianak - Rustam, Rustam; Dulhadi Dulhadi; Cici Herawati (Jurnal Pendidikan Islam Indonesia, 2024)
The development of a website-based questionnaire can retrieve, store and analyze statistical information on the results of self-evaluation of study program. The development of a website-based questionnaire begins with developing an evaluation instrument and developing a template on the website that will be used as a medium to absorb information from respondents. Based on these problems, research questions were formulated: How to develop a website-based survey instrument in IAIN Pontianak's PPG study program?; How to validate a website-based survey instrument in IAIN Pontianak's PPG study program; How are educators' perceptions of study program services in IAIN Pontianak's PPG study program; How are students' perceptions of learning services in IAIN Pontianak's PPG study program? This study used the research and development method. The selection of the method was based on the need to develop a survey instrument using the LimeSurvey application. The respondents consisted of lecturers teaching courses in the study program and students of PPG study program. The results showed that, the components of the LimeSurvey application include the log in page, the survey list page, the survey component editing page, the respondent form page and the survey results statistics page. The developed service instrument received a score of 0.78 ≥ 0.75 with a reliability of 0.922 ≥ 0.05 and the learning service instrument received a score of 0.84 ≥ 0.75 with a reliability of 0.962 ≥ 0.05. Both instruments are declared valid and reliable so that they are suitable for use. The lecturers' perception of the vision and mission of the study program gave an average score of 3.72 on a scale of 4.00 and the study program service management gave a score of 3.62 on a scale of 4.00 so that the vision and mission are relevant and the study program service management is excellent. In the small-scale trial, the score was 3.72 on a scale of 4.00 and in the large-scale trial, the score was 3.56 on a scale of 4.00 so that the learning services in the IAIN Pontianak PPG Study Program were acceptable.